2013
DOI: 10.1063/1.4825043
|View full text |Cite
|
Sign up to set email alerts
|

Faceted growth of primary Al2Cu crystals during directional solidification in high magnetic field

Abstract: The high magnetic field is widely used to modify the crystal morphology. In this work, the effect of the magnetic field on growing behavior of faceted crystals in the Al-40 wt. %Cu alloy was investigated using directional solidification technique. It was found that the faceted growth of primary Al2Cu phase was degraded and the primary spacing was reduced upon applying the magnetic field. Additionally, the length of the mushy zone first decreased and then increased with increase of the magnetic field intensity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Authors suggested that the TEM effect altered the interfacial energy and led to modifications in the solidification microstructure and orientation relationship [46]. In hypereutectic alloys, the effect of an SMF was similar to that observed in hypoeutectic alloys, as shown in Figure 5c [105]. Transverse SMFs triggered inclined solid-liquid interfaces and accelerated segregation, but an external electric current was applied to the sample to induce an electromagnetic (EM) convection, which counteracted the TEM convection and weakened the destruction of solidification microstructure caused by the TEM effect (Figure 5(d1-d3)).…”
Section: Tem Effect During Solidificationmentioning
confidence: 61%
“…Authors suggested that the TEM effect altered the interfacial energy and led to modifications in the solidification microstructure and orientation relationship [46]. In hypereutectic alloys, the effect of an SMF was similar to that observed in hypoeutectic alloys, as shown in Figure 5c [105]. Transverse SMFs triggered inclined solid-liquid interfaces and accelerated segregation, but an external electric current was applied to the sample to induce an electromagnetic (EM) convection, which counteracted the TEM convection and weakened the destruction of solidification microstructure caused by the TEM effect (Figure 5(d1-d3)).…”
Section: Tem Effect During Solidificationmentioning
confidence: 61%
“…In the past two decades, the domain of applying a high magnetic field (HMF) to materials processing has undergone extremely rapid growth since the development of superconducting magnet technology. Especially in the solidification process of materials, HMFs have exhibited a special capacity to modify the crystal growth and thus the final microstructure and crystallography because of the induced Lorentz force, magnetic torque, magnetization energy, etc. Morikawa et al obtained aligned primary dendrite arms of MnBi along the HMF direction in the Bi–Mn alloy. Liu et al reported a decrease of the secondary dendrite arm spacing by the HMF in the solidification of Al–Li alloy.…”
Section: Introductionmentioning
confidence: 99%